2021
DOI: 10.1037/xap0000380
|View full text |Cite
|
Sign up to set email alerts
|

Risky but alluring: Severe COVID-19 pandemic influence increases risk taking.

Abstract: The COVID-19 pandemic has changed our lives to a profound extent. In this research, we examined how the pandemic might have influenced people's general risk attitude in their daily lives. Across four studies (two preregistered) using U.S. online worker and Canadian university student samples, we observed that individuals who were severely affected by the pandemic showed higher risk taking toward a variety of risky activities than those who were less severely affected. We attributed this effect to elevated bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 66 publications
3
8
0
Order By: Relevance
“…Interestingly, the individuals who recovered from the severe disease at primary infection showed a higher reinfection risk when compared with those who present mild symptoms (RR = 1.05, 95% CI 1.01–1.10). Similar findings have been published and may be related to increased perceived benefits from taking risks [ 26 ]. However, only 18 out of 1700 (1.1%) of the enrolled subjects had a severe first infection, so this finding must be considered with caution.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the individuals who recovered from the severe disease at primary infection showed a higher reinfection risk when compared with those who present mild symptoms (RR = 1.05, 95% CI 1.01–1.10). Similar findings have been published and may be related to increased perceived benefits from taking risks [ 26 ]. However, only 18 out of 1700 (1.1%) of the enrolled subjects had a severe first infection, so this finding must be considered with caution.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, individuals who recovered from severe disease at primary infection showed a higher reinfection risk when compared whit those who present mild symptoms (RR = 1.05, 95% CI 1.01 -1.10). Similar findings had been published and may be related to increased perceived benefits from taking risks [10].…”
Section: Discussionsupporting
confidence: 84%
“…Researchers have also shown that the link between the pandemic and risky activities is not limited to the economic domain. For example, a series of correlational studies conducted by Tsai and Zeng (2021) found that participants who had been more severely affected by the ongoing COVID-19 outbreak were more inclined to adopt a risk-seeking attitude toward a wide variety of risky behaviors than those who had been less severely affected. In addition, the researchers provide a theoretical explanation by attributing the relationship uncovered to increased boredom levels and perceived benefits of risky behaviors.…”
mentioning
confidence: 99%